1987
DOI: 10.2136/sssaj1987.03615995005100050043x
|View full text |Cite
|
Sign up to set email alerts
|

Forest Floor and Soil Influence on Response of Douglas‐fir to Urea

Abstract: Data from the Regional Forest Nutrition Research Project (RFNRP) in Washington and Oregon were analyzed to improve stand‐specific prediction of Douglas‐fir [Pseudotsuga menziesii (Mirb.) Franco] response to urea fertilization. The response variable (relative difference in volume growth between fertilized and control plots 4 yr after fertilization with 448 kg N/ha) was regressed against 28 stand and site variables (e.g., age, elevation, forest floor C/N ratio, soil cation exchange capacity, etc.) using stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…'Because a change in forest SOC pools in the Pacific Northwest study area over that period would lessen the utility of the current use of the STATSGO map of SOC, we investigated the possibility of SOC change. The forest floor and surface (0-15 cm) mineral SOC pools in 13 second-growth Douglas-fir stands were measured in 1995 (Hornann et al, 2001 ) and compared with measurements from 1969 to 1970 (Edmonds and Hsiang, 1987;Edmonds and Chappell, 1994). Within each stand, the 1969-1970and Management 220 (2005 270-283 275 values are from a pre-fertilization sampling, and the 1995 values are from a nearby non-fertilized control plot.…”
Section: Change In Soil C Poolsmentioning
confidence: 99%
“…'Because a change in forest SOC pools in the Pacific Northwest study area over that period would lessen the utility of the current use of the STATSGO map of SOC, we investigated the possibility of SOC change. The forest floor and surface (0-15 cm) mineral SOC pools in 13 second-growth Douglas-fir stands were measured in 1995 (Hornann et al, 2001 ) and compared with measurements from 1969 to 1970 (Edmonds and Hsiang, 1987;Edmonds and Chappell, 1994). Within each stand, the 1969-1970and Management 220 (2005 270-283 275 values are from a pre-fertilization sampling, and the 1995 values are from a nearby non-fertilized control plot.…”
Section: Change In Soil C Poolsmentioning
confidence: 99%
“…In the South, the growth response to P fertilization at planting varies dramatically by soil type, primarily determined by geologic formation, soil texture, and drainage class . In the Northwest, Edmonds and Hsiang (1987) showed that the response of Douglas-fir could be partially predicted by the C:N ratio of the forest floor. Carter et al (1998) also found coastal Douglasfir basal area response to fertilization to be related to site index and mineral soil mineralizable-N.…”
Section: The Role Of Forest Soils In Contemporary Forest Managementmentioning
confidence: 99%
“…Several studies have shown that N fertilization of second-and third-rotation Douglas-fir stands can increase tree growth, and such fertilization has become common for increasing forest productivity (Gessel and Walker, 1956;Edmonds and Hsiang, 1987;Stegemoeller and Chappell, 1990;Chappell et al, 1991). Prior studies have shown that observable increases in N availability from N fertilizer generally last no longer than 5-10 years (Binkley and Reid, 1985;Binkley, 1986;Miller, 1988;Strader and Binkley, 1989;Prescott et al, 1995;Priha and Smolander, 1995;Smolander et al, 1998;Nohrstedt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%